INOVASI PEMBUATAN PASTA GIGI ARANG KULIT PISANG - Sadam H.I Hasan; Sri Anggriany Djalil; Herman Herman; Humahera Yanti; Firman Menne (Jurnal Ilmiah Ecosystem, 2021)
Banana peel, whose use is unknown to the wider community, has economic value if it is processed into toothpaste which can be used as a source of income for students and the surrounding community. Through the Student Creativity Program, it is hoped that it can become an innovation in creating business opportunities among students by utilizing simple technology in making pasta products from banana peel charcoal. The process consists of several production stages, namely pre-production, production and post-production. The marketing process is carried out by developing an electronic transaction system using media (online) based on the PO (Pre Order) system.